2014
DOI: 10.1016/j.juro.2013.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Evaluation of Urolithiasis and Obesity in a Midwestern Pediatric Population

Abstract: Our results do not confirm obesity as a risk factor for pediatric urolithiasis in otherwise healthy patients. We also found no substantial metabolic differences between healthy nonobese stone formers and obese patients. While the pediatric literature is mixed, our study supports the majority of published series that have failed to establish a link between pediatric urolithiasis and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…17 Additional studies on pediatric urolithiasis reached the same conclusion. 3,21 In the current study, although American children were heavier (Table 2), the percentage of those being overweight did not exceed the percentage in the general pediatric school-age population of 17.0% per recent data from the Centers for Disease Control and Prevention. 22 Although national data regarding obesity in the Brazilian pediatric population were not fully available, a recent school-based cross-sectional study by Silva et al 23 involving 41 654 students showed that the growth in body weight, height, and BMI in urban areas is increasingly similar to those reported in developed countries.…”
Section: Discussionmentioning
confidence: 43%
“…17 Additional studies on pediatric urolithiasis reached the same conclusion. 3,21 In the current study, although American children were heavier (Table 2), the percentage of those being overweight did not exceed the percentage in the general pediatric school-age population of 17.0% per recent data from the Centers for Disease Control and Prevention. 22 Although national data regarding obesity in the Brazilian pediatric population were not fully available, a recent school-based cross-sectional study by Silva et al 23 involving 41 654 students showed that the growth in body weight, height, and BMI in urban areas is increasingly similar to those reported in developed countries.…”
Section: Discussionmentioning
confidence: 43%
“…Eisner et al found that as BMI increased, urine oxalate excretion decreased and super-saturation of calcium phosphate increased [18]. Other recent studies support that there may be no substantial metabolic differences between healthy non-obese and obese stone formers [19][20][21]. In contrast, another retrospective study found that overweight and obese stone forming children were more likely to have decreased levels of urine citrate, phosphate, and magnesium and increased hypercalcuria when compared with patients with normal BMI [22].…”
Section: Discussionmentioning
confidence: 98%
“…Another study found no significant relationship between BMI and urolithiasis, but did find a significant decrease in the odds of urolithiasis in black race and Medicaid payer status [13]. While the aforementioned studies collectively do not identify a definitive relationship between obesity and kidney stones in children, longitudinal studies may be warranted [2,[14][15][16][17][18].…”
Section: Epidemiologymentioning
confidence: 99%